Platelet-Rich Plasma and Er: YAG Laser Therapy for Female Stress Urinary Incontinence: A Systematic Review: Platelet-Rich Plasma and Er: YAG Laser Therapy for Female Stress Urinary Incontinence: A Systematic Review - Rahman, Misbah Ur; Ahmad, Waqas; Idrees, Sana; Nadeem, Wajeeha; Khan, Rabia; Liaqat, Zarmeena (Pakistan Journal of Health Sciences, 2026)
Female stress urinary incontinence (SUI) is a prevalent condition that negatively affects quality of life. Although surgery is effective, concerns related to morbidity and patient reluctance have increased interest in minimally invasive treatment options. Objectives: To systematically evaluate clinical evidence on the effectiveness and safety of platelet-rich plasma (PRP) injections and non-ablative Er: YAG vaginal laser therapy in women with stress urinary incontinence. Methods: This systematic review followed PRISMA 2020 guidelines. PubMed/MEDLINE, Scopus, and the Cochrane Library were searched for studies published between January 2018 and March 2025. Randomized controlled trials and prospective interventional cohort studies involving adult women with SUI were included. Data were extracted on validated symptom scores, objective outcomes, adverse events, and treatment effects. Risk of bias was assessed using Cochrane RoB-2 and NIH tools. Due to heterogeneity, results were synthesized narratively. Results: Ten studies (six randomized trials and four cohort studies) were included. Both PRP and Er: YAG laser therapy demonstrated improvement in symptom severity using validated patient-reported and objective measures. Sham-controlled trials generally favored active treatment, while combined PRP and pelvic floor muscle training showed greater benefit. Most randomized trials had some risk of bias, and cohort studies were of fair quality. Conclusions: PRP injections and Er: YAG vaginal laser therapy are promising minimally invasive options for selected women with mild to moderate SUI, though further high-quality trials are needed to confirm long-term effectiveness.